Предмет: Алгебра,
автор: 1qwPolk
1.5(x-2)-2(3-1.5x)
x=-0,2
Приложения:
Ответы
Автор ответа:
2
1.5х-3-6+3х=4.5х-9
4.5*(-0.2)-9=-0.9-9= -9.9
4.5*(-0.2)-9=-0.9-9= -9.9
Автор ответа:
2
Решение:
1,5•(x - 2) - 2•(3 - 1.5x) = 1.5,х - 3 - 6 + 3х = 4,5х - 9.
Если х = - 0,2, то 4,5•(- 0,2) - 9 = - 0,9 - 9 = - 9.9
1,5•(x - 2) - 2•(3 - 1.5x) = 1.5,х - 3 - 6 + 3х = 4,5х - 9.
Если х = - 0,2, то 4,5•(- 0,2) - 9 = - 0,9 - 9 = - 9.9
1qwPolk:
спасибо
Похожие вопросы
Предмет: Биология,
автор: zaicevavasilisa
Предмет: История,
автор: zopagomunkula0
Предмет: Окружающий мир,
автор: vikysiayumat25
Предмет: Математика,
автор: rik22